Emergence, diffusion et déclin d’un réseau de cliniques franchisées en Inde - Bertrand Lefebvre (Unité Mixte de Recherche 8504 Géographie-cités, 2015)
Franchising has become a common strategy in the development of commercial networks. While management science has long been interested in the reasons for choosing franchising, geography has shown little interest in this particular form of network’s control and its impact on the spatial diffusion of these networks. The present paper analyses the reasons for an Indian company to expand its network of clinics through franchising and the consequences on its spatial distribution. Considering the effect of distance, what strategies are designed to control a network of franchises? Our methodology is based on semi-structured interviews with franchisees and management of the network coupled with the development of a database to study the spatial distribution of the network in India’s urban system. After an initial phase of rapid diffusion, network development was slowed down and later stagnated until the company finally dropped the franchise model for an internal growth model.